Model Matematika Zakat dalam Pengurangan Kemiskinan - Lani Widia Putri; muhammad subhan; Media Rosha (Journal of Mathematics UNP, 2018)
Abstract –Poverty is condition where people have lack of income to fulfill basic living needs. The condition is cause by some reasons like less of natural resources, less of human resources, and less of financial. Zakah is a effort to poverty decrement. To determine the factors that should be improved that we use mathematical model. Mathematical model of zakah in form of nonlinear differential equation system. Based on analysis of factor model  than influence poverty decrement are zakah influence level, business success level, and interaction level. The simulation it looks interaction level is more large to reach stability than other factors, it means that more height the interaction level makes more optimum to poverty decrement.